Конец света: [роман] / Сидни Шелдон ; пер. с англ. А. П. Романова - Шелдон Сидни (Мировой бестселлер, 1993)
Экземпляры: Ф. 10 (20200727) / Инвентарный номер: 47945 / Цена: 25.00 / Сис.шифр: 84(4/8) / Авт.знак: Ш 42 / ГРНТИ: 17.82 / ББК: 84(7Сое)